Terahertz Resonance Fluorescence of a Spherical Gaussian Quantum Dot - Behrooz Vaseghi; Ghasem Rezaei; Nasim Mohammadi; Shakiba Mardani (Journal of Optoelectronical Nanostructures)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!-- [if gte mso 9]> <w:LsdException Locked="false" Priority="51"